Pengaruh Pemberian Pupuk Kotoran Ayam dan Urea terhadap Pertumbuhan dan Hasil Tanaman Bawang Daun pada Tanah Gambut Pedalaman: Effect of Chicken Manure Fertilizer and Urea on Plant Growth and Yield Leaf Onion (Allium fistulosum L.) in the Inland Peat Soil - Pantie, Fredy Agus Saputra; Atikah, Titin Apung; Widiastuti, Lusia (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
The purpose of this study was to determine the effect of chicken manure and urea on the growth and yield of onion leaves on inland peat soil. The design used was a Completely Randomized Design (CRD) factorial with two treatment factors. The first factor is that chicken manure fertilizer application consists of 4 levels, namely: 0, 5, 10 and 15 tons/ha, and the second factor is the provision of urea that consists of 3 levels, namely: 0, 125 and 250 kg/ha. The variables measured were plant height and fresh weight of the leaves of onion plants. The results showed that the interaction between chicken manure and urea fertilizer had no significant effect on all variables observed at all ages observed. Single factor giving 15 tons/ha of chicken manure fertilizer showed growth and better results on the average variable plant height and fresh weight of the leaves of onion plants in inland peat soil. Single factor giving of urea 250 kg/ha showed growth and better results on the average variable plant height and fresh weight of onion plants in inland peat soil.